The Illusion of Consent: Hegemony and Resistance in Ama Ata Aidoo’s Our Sister Killjoy - Shah, Syeda Aliya; Tariq, Rabia (Pakistan Languages and Humanities Review, 2025)
This research paper examines Ama Ata Aidoo’s Our Sister Killjoy (1977) to expose postcolonial African elites being ideologically framed by Western worldviews, thereby perpetuating cultural and psychological domination even in the absence of physical colonization. The primary objective is to investigate the mental conditioning of African self-exiles who adopt and internalize Western ideologies with little resistance, reinforcing a passive form of consent. The secondary aim is to examine the process by which this internalization occurs, thereby revealing the subtle mechanisms of neocolonial control. It critiques the postcolonial notions of hegemony and consent through Sissie’s experiences in Europe and her reflections on neocolonial Africa. A qualitative research design is employed using textual analysis of Aidoo’s novel as the primary data source. The research is grounded in Antonio Gramsci’s theory of cultural hegemony and consent. Key findings reveal that the illusion of consent is maintained through ideological conditioning that frames Western values as universal and superior. They are presented under the guise of politeness or modernity, not through coercion.